Program Pemberian Makanan Berdasarkan Kebutuhan Protein dan Energi pada Setiap Fase Pertumbuhan Ayam Poncin - D M Suci; E Mursyida; T Setianah; R Mutia (Faculty of Animal Science, Bogor Agricultural University, 2005)
An experiment was conducted to study the effect of feeding program to Poncin chicken (crossbred Arab chicken and Kedu Chicken) based on energy and protein requirement on growing period 1-4, 4-8 and 8-12 weeks. One week age sixty chickens were used in this experiment. This experiment consisted of three treatments based on the age of the chicken, P1= 1-8; 8-12 weeks old was used R1 ( ME 2800 kcal/kg, CP 20 ); R3 (ME 2400 kcal/kg, CP 16% ); P2 = 1-4, 4-8, 8-12 weeks old was used R1, R2(2600 kcal/kg, CP 18% ) and R3 ; P3= 1-4, 4-8, 8-12 weeks old was used R1, R3, R4 (ME 2400 kcal/kg, CP 14%). Completely randomized design was used in this experiment. Data were analysed by varian. The results indicated that P1 feeding program was the best for body weight gain (888.46 vs 812.62; 736.93 gram/bird) and low of feed conversion ratio (3.92 vs 4.02; 4.53) compared to P2 and P3 programs. Abdominal fat percentage was the lowest by P3 feeding program compared to P1 and P2 programs (0.22% vs 0.72%; 0.55%). Key words : feeding program, protein and energy requirement, growing period, Poncin Chicken